Space-Charge Effect on the Theoretical Design of Electron Gun Operated under Zero Magnification Condition - Baghdad Science Journal (مجلة بغداد للعلوم)
A computational investigation is carried out in the field of charged –particle optics with the aid of numerical analysis method using the personal computer. The work is concerned with the design of electron gun with space-charge effect. The Finite element method (FEM) used in the solution of Poison's equation for determine the axial potential distribution of the two-electrode immersion lens operated under zero magnification condition , and from the solution of the paraxial ray equation the optical properties such as the focal length , spherical and chromatic aberration coefficients are determined, also a calculation of the brightness and perveance for the lens. The electrodes geometry was determined in two and three dimension with the aid of new drawing software called SIMION 7 and the electron beam trajectory under zero magnification conditions has been determine for these electrodes.